TELA’AH FILSAFAT ARTHUR SCHOPENHAUER TENTANG PENDIDIKAN - Muhammad Agus Nurohman; Fuad Efendi; Muhammad Bahrul Ulum (STAI Darussalam Lampung, 2024)
The purpose of this article is to discuss the concept of Arthur Schopenhauer's philosophy of education. The research is literature, the method of data collection is documentation and the analysis used is content analysis. The result of the research is that Arthur Schopenhauer, who was born in Danzig (now Gdansk) in 1788 and died in Frankfurt-am-Main in 1860, has always been a stranger among philosophers. He was considered too literary and rhetorical by analytical philosophers, too metaphysical by logical positivists and scientific naturalists, and too unhistorical and apolitical for Hegelians and phenomenologists. The school was pioneered by Arthur Schopenhauer (1768-1860), and is famous for its theory of talent. In essence, nativism stems from the Leibnitzian Tradition which emphasises the inner abilities of a child, therefore environmental factors including educational factors have less influence on the development of children. The results of development are determined by the innate and genetic characteristics of both parents. This school holds the view that individual development is determined by innate factors from birth. Environmental factors have less influence on education and child development. Therefore, the outcome of education is determined by the talent brought from birth.